DIVERSIDAD Y ABUNDANCIA DE MURCIELAGOS SEGÚN LA VARIACION ALTITUDINAL, EN EL ANP SANTUARIO NACIONAL TABACONAS NAMBALLE. SAN IGNACIO, CAJAMARCA, 2018. - Fuentes Pizarro, Esthefanie (2018)
Having data such as diversity and abundance with respect to biological conservation is invaluable; The documents are based on bat records regarding the altitudinal variation in the National Sanctuary of ANP Tabaconas in the poor, so it is the Tabaconas Citizenship Network in the ANP. Ignacio, Cajamarca, during the period from September to December 2018, which is located on primary forests, secondary forests, virgin forest and we stopped. The changes of speed have been reduced to four times of place; These were extended from 18:00 to 24:00 hours. It was possible to register 6 different species, from the same family Phyllostomidae, the species Carollia perspicillata was the most abundant. According to the Shannon index, the highest diversity is found in stratum B (Hꞌ = 1,714) and C (Hꞌ = 1,709) being very similar and lower in stratum D (Hꞌ = 1,494), considering themselves normal. The nonparametric estimators; Chao 1, Jackniffe 1 and Boobstrap, indicate that 100% representativeness in the six strata. According to the current legislation of Supreme Decree N ° 004-2014-MINAGRI and both international agreements; CITES 2013 and IUCN 2018-2, none of the species observed in the investigation is threatened. KEY WORDS: